Highly sensitive-pin-accessibility for ATM using human body communication - Balamurugan, M; Amarnath. J, Jegan; Kumar Sahoo, Pradeep; Anand M, Suresh; Soorya, C; ., Subham; Sathyan, D (International Journal of Engineering and Technology, 2018)
Burglary of ATM have increased in recent days which led to the use of biometrics to get high level of security and accuracy. This paper defines a system that replaces the ATM cards and PINs by using a new technology. A system is proposed for secured transaction in ATM machine. The technology used in this process is called as Red-Tacton. This contains Transmitter and Receiver section which transmits the dataâ€™s through human body. Initially user needs to keep the fingerprint to access the ATM. The user must hold the transmitter module where the userâ€™s password (PIN) is stored. When the user touches the receiver in ATM, pin is transferred from the transmitter to the receiver using human body as the medium. The temperature sensor used to detect the fire accident in the ATM activates the water pump motor to extinguish the fire. The MEMS sensor store the measurements of x-y-z axis of the ATM machine and used to find out if any theft in ATM or Vibration above the threshold level automatically shutter will be closed. Also the intimation is given via buzzer.Â